Selective laser melting forming method for AlSi10Mg aluminum alloy composite powder

By adding Ni-Ti powder to the Alsi10mg aluminum alloy powder, and using laser selection melting molding and thermal treatment process, the ALSI10mg aluminum alloy has a large problem of residual stress during the laser melting process of the constituency. The molding effect of heat resistance.

CN119368760APending Publication Date: 2025-01-28FUJIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505248.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the selection laser melting and forming process, AlSi10Mg aluminum alloy has a significant residual stress due to a large temperature gradient, which affects the shape and dimensional accuracy, safety and corrosion resistance of the parts.

Method used

The laser constituency melting method of ALSI10mg aluminum alloy composite powder is used, and 1.5WT.%Ni-Ti powder is added to the ALSI10mg powder to mix, dry and the laser laser melting molding, and subsequently heat treatment.

Benefits of technology

Effectively improve the laser absorption rate of molding powder, improve the quality of molding, realize the fineness of grains, and improve the mechanical properties and thermal resistance of ALSI10mg aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a selective laser melting forming method of AlSi10Mg aluminum alloy composite powder. The AlSi10Mg aluminum alloy composite powder comprises the following components in percentage by mass: 1.5 wt% of Ni-Ti powder and the balance of AlSi10Mg aluminum alloy powder. The forming method comprises the following steps that (1) Ni-Ti powder and AlSi10Mg aluminum alloy powder with the corresponding mass are weighed according to the proportion; (2) the Ni-Ti powder and the AlSi10Mg aluminum alloy powder are put into a tank mill to be mixed; (3) putting the composite powder obtained in the step (2) into a vacuum drying oven for drying; (4) the dried composite powder in the step (3) is put into metal additive manufacturing equipment to be formed, and a sample piece is obtained; and (5) carrying out heat treatment on the formed sample piece obtained in the step (4). The nucleating agent solid spherical Ni-Ti powder is adopted, grain refinement is achieved, and meanwhile the mechanical property of the AlSi10Mg aluminum alloy under thermal exposure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal additive manufacturing, and in particular relates to a laser selective melting forming method for AlSi10Mg aluminum alloy composite powder. Background Art

[0002] Selective laser melting (SLM) technology is a cost-effective and emerging additive manufacturing technology in the field of additive manufacturing (AM). It is widely used in many industries because it can quickly manufacture high-performance components with complex shapes and high precision. Traditional manufacturing technology faces problems such as low precision, long cycle and difficulty in molding complex components. However, selective laser melting (SLM) technology uses computer-designed three-dimensional model components, uses slicing software to divide and slice the layer thickness, and finally integrates the complex shape components by adding each layer. There are many types of metal materials that can be used for selective laser melting (SLM) molding, including Cu, Al, Ti alloys and Ni high-temperature alloys, which has led to its extensive application in aerospace, automobiles and medicine.

[0003] However, due to the extremely large temperature gradient of AlSi10Mg aluminum alloy during the forming process, the residual stress is obvious, which has an adverse effect on the shape and dimensional accuracy, safety and corrosion resistance of the parts, and cannot meet the industrial requirements. Summary of the invention The present invention aims to improve the problems existing in the above-mentioned prior art, that is, the technical problem to be solved by the present invention is to provide a laser selective melting forming method for AlSi10Mg aluminum alloy composite powder.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a laser selective melting molding method of AlSi10Mg aluminum alloy composite powder, wherein the components of the AlSi10Mg aluminum alloy composite powder are as follows: 1.5wt.% Ni-Ti powder and the balance AlSi10Mg aluminum alloy powder; the molding method comprises the following steps: (1) Weigh out the corresponding masses of Ni-Ti powder and AlSi10Mg aluminum alloy powder according to the proportion; (2) putting Ni-Ti powder and AlSi10Mg aluminum alloy powder into a pot mill for mixing; (3) placing the composite powder obtained in step (2) in a vacuum drying oven for drying; (4) placing the composite powder dried in step (3) into a metal additive manufacturing device to form a sample; (5) Heat treating the molded sample obtained in step (4).

[0006] Furthermore, the AlSi10Mg aluminum alloy powder is a solid sphere with a particle size of 15 to 53 μm; the Ni-Ti powder particles are a solid sphere with a particle size of 8 μm.

[0007] Furthermore, in step (2), the rotation speed of the jar mill is 100 rpm and the jar mill time is 3 hours.

[0008] Furthermore, in step (3), the vacuum drying oven is evacuated, the drying temperature of the vacuum drying oven is 60° C. to 80° C., and the drying time is 3 to 6 hours.

[0009] Furthermore, the process parameters of the selected area laser melting molding in step (4) are as follows: laser power is 200-400 W, scanning speed is 1200-2000 mm / s, scanning spacing is 80-110 μm, powder thickness is 20-30 μm, the substrate is an aluminum alloy substrate, the substrate preheating temperature is 180-200°C, the scanning angle of adjacent powder layers is rotated 67°, and the molding chamber uses argon gas with an oxygen content of less than 100 ppm.

[0010] Furthermore, the heat treatment process in step (5) is long-term aging treatment and solution treatment.

[0011] Furthermore, the parameters of aging treatment are: 150℃, 200℃, 300℃, and keep warm for 100h; the parameters of solution treatment are: 540℃, keep warm for 2h, increase the temperature to 540 at 5-10℃ / h, water quench to room temperature, and the transfer time is less than 10s; the regression aging temperature is 150℃, and the aging time is 100h.

[0012] Compared with the prior art, the present invention has the following effects: the present invention is reasonably designed, and by adding foreign particles or alloy elements to the AlSi10Mg powder formed by selective laser melting, the laser absorption rate of the forming powder can be effectively improved, and the forming quality in the selective laser melting forming process can be effectively improved; the solid spherical Ni-Ti powder used as the nucleating agent can achieve grain refinement and improve the mechanical properties of the AlSi10Mg aluminum alloy under thermal exposure. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The particle size, shape scanning electron microscope image and powder particle size distribution diagram of the two powders used in the embodiments of the present invention are shown in FIG. Figure (a) is a scanning electron microscope image of AlSi10Mg aluminum alloy powder; Figure (b) is a scanning electron microscope image of Ni-Ti / AlSi10Mg alloy powder particles; Figure (c) is a particle size distribution diagram of AlSi10Mg alloy powder; Figure 2 This is a microstructure diagram of a sample formed by selective laser melting in Example 1 of the present invention; Figure 3This is a microstructure diagram of a sample formed by laser melting in selected area of ​​comparative example 1 of the present invention; Figure 4 This is a microstructure diagram of corrosion of a sample formed by selective laser melting in Example 1 of the present invention; Figure 5 This is a microstructure diagram of corrosion of a sample formed by laser melting in a selected area in comparative example 1 of the present invention; Figure 6 This is a TEM bright field (BF) image of a sample formed by selective laser melting in Example 1 of the present invention; Figure 7 This is the TEM bright field (BF) image of the sample formed by selected area laser melting in comparative example 2 of the present invention. DETAILED DESCRIPTION The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0015] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicating orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0016] The present invention discloses a laser selective melting molding method for AlSi10Mg aluminum alloy composite powder, wherein the AlSi10Mg aluminum alloy composite powder comprises the following components by mass percentage: 1.5 wt.% Ni-Ti powder and the remainder AlSi10Mg aluminum alloy powder; the molding method comprises the following steps: (1) Weigh out the corresponding masses of Ni-Ti powder and AlSi10Mg aluminum alloy powder according to the proportion; (2) putting Ni-Ti powder and AlSi10Mg aluminum alloy powder into a pot mill for mixing; (3) placing the composite powder obtained in step (2) in a vacuum drying oven for drying; (4) placing the composite powder dried in step (3) into a metal additive manufacturing device to form a sample; (5) Heat treating the molded sample obtained in step (4).

[0017] In this embodiment, the AlSi10Mg aluminum alloy powder is a solid sphere with a particle size of 15 to 53 μm.

[0018] In this embodiment, the Ni-Ti powder particles are solid spherical and have a particle size of 8 μm.

[0019] In this embodiment, the rotation speed of the pot mill in step (2) is 100 rpm, and the pot mill time is 3 hours.

[0020] In this embodiment, in step (3), the vacuum drying oven is evacuated, the drying temperature of the vacuum drying oven is 60° C. to 80° C., and the drying time of the vacuum drying oven is 3 to 6 hours.

[0021] In this embodiment, the process parameters of the selected area laser melting molding in step (4) are as follows: laser power is 200-400 W, scanning speed is 1200-2000 mm / s, scanning spacing is 80-110 μm, powder thickness is 20-30 μm, the substrate is an aluminum alloy substrate, the substrate preheating temperature is 180-200°C, the scanning angle of adjacent powder layers is rotated 67°, and the molding chamber uses argon gas with an oxygen content of less than 100 ppm.

[0022] In this embodiment, the heat treatment process in step (5) is long-term aging treatment and solution treatment. The parameters of the aging treatment are: 150°C, 200°C, 300°C, and insulation for 100 hours; the parameters of the solution treatment are: 540°C, insulation for 2 hours, heating to 540 at a rate of 5-10°C / h, water quenching to room temperature, and transfer time <10s; the regression aging temperature is 150°C, and the aging time is 100 hours.

[0023] By adding foreign particles or alloying elements to the AlSi10Mg powder formed by selective laser melting, the laser absorption rate of the forming powder can be effectively improved, and the forming quality in the SLM process can be improved. During the selective laser melting process, foreign elements tend to be over-melted in the matrix, and react in situ inside the matrix to generate a second phase. The formed second phase can act as a nucleation point inside the matrix to hinder grain growth, thereby achieving the purpose of refining grains and eliminating cracks. The addition of Ni-Ti significantly refines the grains of the AlSi10Mg alloy formed by selective laser melting to 2.9um and eliminates the texture in the AlSi10Mg alloy. This is because during the selective laser melting process, the Al3Ti generated by the in-situ reaction of Ni-Ti and α-Al acts as a heterogeneous nucleation site and promotes non-uniform nucleation. In addition, after the addition of Ni-Ti, no Si network is observed. In addition to being segregated at the grain boundary with Ni, the Si element also forms a large number of nano-scale Si precipitates inside the grains.

[0024] The solid spherical Ni-Ti powder as a nucleating agent adopted in the present invention realizes grain refinement and improves the mechanical properties of the AlSi10Mg aluminum alloy under heat exposure.

[0025] The present invention prepares an AlSi10Mg sample with fine and uniform structure and excellent mechanical properties through selective laser melting technology, and then undergoes a suitable heat treatment process to effectively improve the tensile properties and elongation, so that good mechanical properties are maintained under heat exposure.

[0026] The composition of the AlSi10Mg aluminum alloy powder used in the following examples and comparative examples is shown in Table 1 below.

[0027] Table 1 Chemical composition of AlSi10Mg aluminum alloy powder (mass fraction / %) Example 1 Step S1: weighing out powder according to the ratio of 1.5 wt.% Ni-Ti + 98.5 wt.% AlSi10Mg aluminum alloy for later use; Step S2: The powder weighed in step S1 is mixed in a jar mill at a rotation speed of 100 rpm for 3 hours; then dried in a vacuum drying oven at a temperature of 70° C. for 6 hours; Step S3: The composite powder dried in step S2 is subjected to selective laser melting molding: molding process parameters: laser power is 350W, scanning speed is 1400mm / s, scanning spacing is 110μm, powder thickness is 30μm, substrate is aluminum alloy substrate, substrate preheating temperature is 200℃, adjacent powder layer scanning angle is rotated 67°, molding chamber uses argon gas, oxygen content is less than 100ppm; no heat treatment is performed on the printed molded parts. Mechanical properties of the sample: tensile strength is 441.2MPa, yield strength is 252.7MPa, and elongation is 4.6%.

[0028] Comparative Example 1 Step S1: weigh a certain amount of AlSi10Mg aluminum alloy raw powder for later use; Step S2: Dry the raw powder weighed in step S1, evacuate the vacuum drying oven, the drying temperature is 70°C, and the drying time is 6 hours. Then perform selective laser melting molding: molding process parameters: laser power is 350W, scanning speed is 1400mm / s, scanning spacing is 110μm, powder thickness is 30μm, substrate is aluminum alloy substrate, substrate preheating temperature is 200℃, adjacent powder layer scanning angle is rotated 67°, molding chamber uses argon gas, oxygen content is 100ppm, and no heat treatment is performed on the printed molded parts. Mechanical properties of the sample: tensile strength is 373MPa, yield strength is 197.7MPa, and elongation is 5.3%.

[0029] Comparative Example 2 Step S1: weighing out powder according to the ratio of 1.5 wt.% Ni-Ti + 98.5 wt.% AlSi10Mg aluminum alloy for later use; Step S2: The powder weighed in step S1 is mixed by a mechanical powder mixer (jar mill), the speed of the mechanical powder mixer is 100 rpm, and the jar milling time is 3 hours; then the powder is dried by vacuum drying in a vacuum drying oven, the drying temperature is 70°C, and the drying time is 6 hours; Step S3: performing selective laser melting molding on the composite powder dried in step S2: molding process parameters: laser power of 350W, scanning speed of 1400mm / s, scanning spacing of 110μm, powder thickness of 30μm, substrate of aluminum alloy substrate, substrate preheating temperature of 200℃, adjacent powder layer scanning angle rotated by 67°, argon gas was used in the molding chamber, and the oxygen content was less than 100ppm; Step S4: heat treatment and aging treatment are performed on the printed parts at 300°C for 2h. The mechanical properties of the samples are as follows: tensile strength is 350.3MPa, yield strength is 189.5MPa, and elongation is 4.7%.

[0030] Comparative Example 3 Step S1: weigh a certain amount of AlSi10Mg aluminum alloy raw powder for later use; Step S2: Dry the raw powder weighed in step S1, evacuate the vacuum drying oven, the drying temperature is 70°C, and the drying time is 6 hours. Then perform selective laser melting molding: molding process parameters: laser power is 350W, scanning speed is 1400mm / s, scanning spacing is 110μm, powder thickness is 30μm, substrate is aluminum alloy substrate, substrate preheating temperature is 200℃, adjacent powder layer scanning angle is rotated 67°, molding chamber uses argon gas, oxygen content is 100ppm, and the printed molded parts are heat treated and aged at 300℃ for 2h. Mechanical properties of the sample: tensile strength is 303.7MPa, yield strength is 188.9MPa, and elongation is 4.7%.

[0031] The particle size of AlSi10Mg aluminum alloy powder and the electron microscope image of Ni-Ti powder are shown in Figure 2. Figure 1 As shown in FIG. 1 , the density of the sample prepared by selective laser melting in Example 1 is 98.5%, and a picture of the surface of the sample is obtained by an optical microscope, as shown in FIG. Figure 2 As shown, it can be seen that there are no thermal cracks on the surface of the sample, only a very small amount of gas holes, and its hardness is 145.7HV; the density of the sample prepared by laser selective melting in comparative example 1 is 99.6%, as shown in Figure 3As shown, it can be seen that the sample surface is well formed and its hardness is 140.3HV. After the sample prepared by selective laser melting in comparative example 2 and the sample prepared by selective laser melting in comparative example 3 were subjected to 300℃ / 2h, the hardness of comparative example 2 was 122HV, and the hardness of comparative example 3 was 99.6HV. The tensile test was carried out on the samples of embodiment 1, comparative example 1, comparative example 2 and comparative example 3, and the mechanical properties are shown in the following table 2.

[0032] Table 2 Comprehensive performance of samples The advantages of the present invention are: (1) The solid spherical Ni-Ti powder used as the nucleating agent, in the printing process, reacts in situ with α-Al to generate Al3Ti, which acts as a heterogeneous nucleation site, promoting non-uniform nucleation and achieving grain refinement. In addition, after the addition of Ni-Ti, no Si network was observed. In addition to being segregated at the grain boundary with Ni, the Si element also forms a large number of nano-scale Si precipitates inside the grains, eliminating the texture in the AlSi10Mg alloy and improving the mechanical properties of the AlSi10Mg aluminum alloy. (2) AlSi10Mg aluminum alloy is a heat-treatable aluminum alloy. The heat treatment process includes long-term aging and solution aging. The addition of Ni-Ti improves the heat resistance of AlSi10Mg alloy and reduces the attenuation of its mechanical properties at 300℃ annealing temperature. The aggregation of Si and Ni at the grain boundaries effectively hinders the growth of Ni-Ti / AlSi10Mg alloy grains at 300℃. After 300℃ / 120 min, the yield and tensile strengths of Ni-Ti / AlSi10Mg alloy still reach 189.5MPa and 350.3MPa, which are significantly higher than 188.9MPa and 303.7MPa of AlSi10Mg.

[0033] If the present invention discloses or involves components or structures that are fixedly connected to each other, then, unless otherwise stated, the fixed connection can be understood as: a detachable fixed connection (for example, connection using bolts or screws), and can also be understood as: a non-detachable fixed connection (for example, riveting, welding). Of course, the mutual fixed connection can also be replaced by an integrated structure (for example, manufactured by one-piece molding using a casting process) (except when it is obviously impossible to use an one-piece molding process).

[0034] In addition, unless otherwise stated, the terms used to indicate positional relationships or shapes in any of the technical solutions disclosed in the present invention include states or shapes that are approximate, similar, or close to them.

[0035] Any component provided by the present invention may be assembled from a plurality of separate components, or may be a separate component manufactured by an integral forming process.

[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A laser selective melting method for AlSi10Mg aluminum alloy composite powder, characterized in that: The AlSi10Mg aluminum alloy composite powder comprises the following components by mass percentage: 1.5 wt.% Ni-Ti powder and the remainder AlSi10Mg aluminum alloy powder; the molding method comprises the following steps: (1) Weigh out the corresponding masses of Ni-Ti powder and AlSi10Mg aluminum alloy powder according to the proportion; (2) putting Ni-Ti powder and AlSi10Mg aluminum alloy powder into a pot mill for mixing; (3) placing the composite powder obtained in step (2) in a vacuum drying oven for drying; (4) placing the composite powder dried in step (3) into a metal additive manufacturing device to form a sample; (5) Heat treating the molded sample obtained in step (4).

2. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 1, characterized in that: The AlSi10Mg aluminum alloy powder is a solid sphere with a particle size of 15 to 53 μm; the Ni-Ti powder particles are a solid sphere with a particle size of 8 μm.

3. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 1, characterized in that: In step (2), the rotation speed of the jar mill is 100 rpm and the jar milling time is 3 hours.

4. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 1, characterized in that: In step (3), the vacuum drying oven is evacuated, the drying temperature of the vacuum drying oven is 60° C. to 80° C., and the drying time is 3 to 6 hours.

5. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 1, characterized in that: The process parameters of the selected area laser melting molding in step (4) are as follows: laser power is 200-400 W, scanning speed is 1200-2000 mm / s, scanning spacing is 80-110 μm, powder thickness is 20-30 μm, the substrate is an aluminum alloy substrate, the substrate preheating temperature is 180-200°C, the scanning angle of adjacent powder layers is rotated 67°, and the molding chamber uses argon gas with an oxygen content of less than 100 ppm.

6. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 1, characterized in that: The heat treatment process in step (5) is long-term aging treatment and solution treatment.

7. The laser selective melting forming method of AlSi10Mg aluminum alloy composite powder according to claim 6, characterized in that: The parameters of aging treatment are: 150℃, 200℃, 300℃, keeping warm for 100h; the parameters of solution treatment are: 540℃, keeping warm for 2h, heating to 540 at 5-10℃ / h, water quenching to room temperature, transfer time <10s; regression aging temperature is 150℃, and aging time is 100h.